Four‐Dimensional Materials: Induction of Four‐Dimensional Spatiotemporal Geometric Transformations in High Cell Density Tissues via Shape‐Changing Hydrogels (Adv. Funct. Mater. 24/2021). (10th June 2021) - Lee, Yu Bin; Jeon, Oju; Lee, Sang Jin; Ding, Aixiang; Wells, Derrick; Alsberg, Eben
Abstract : In article number 2010104, Eben Alsberg and co‐workers report the engineering of 4D high cell density constructs (1.0 × 10 8 cells mL −1 ) that change their shape over time by exploiting temporal differences in swelling rates between two biodegradable and cytocompatible materials. This strategy presents a paradigm changing platform technology that could significantly impact 4D tissue‐engineered therapeutics for the treatment of damaged tissues, investigation of questions in developmental biology, and formation of tissue models for drug testing.